2013
DOI: 10.3109/10826084.2013.824473
|View full text |Cite
|
Sign up to set email alerts
|

Let's Get This Party Started: The Effects of Descriptive and Injunctive Norms on Preparty Behavior in College Students

Abstract: Participants (N = 202) were students at a college in the northeastern United States who participated in the 2010 Core Alcohol and Drug survey. Data were collected on prepartying behavior, preparty social norms, and individual-difference variables. Using multivariate logistic and least-squares regression, it was found that descriptive social norms were associated with prepartying in women and injunctive social norms were associated with prepartying in men. Prepartying also was found to be negatively related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…This research has uncovered both practical (to save money, avoid arrest) and enhancement (enjoy evening more, facilitate intimacy) motives for pregaming, and both measures could provide rich topics of feedback or discussion in the content of an intervention. Finally, college students overestimate the frequency and quantity of pregaming by peers (Pedersen & LaBrie, 2008), as well as peer approval (Rutledge, McCarthy, & Lendyak, 2014), resulting in perceptions of a permissive social context for pregaming. Thus, providing corrective normative feedback on overestimations of pregaming among similar peers may be expected to alter students’ perceptions of how often their peers drink and how much alcohol they consume while doing so, in which case changes in pregaming norms may also be expected to change, and perhaps mediate, intervention effects on pregaming behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This research has uncovered both practical (to save money, avoid arrest) and enhancement (enjoy evening more, facilitate intimacy) motives for pregaming, and both measures could provide rich topics of feedback or discussion in the content of an intervention. Finally, college students overestimate the frequency and quantity of pregaming by peers (Pedersen & LaBrie, 2008), as well as peer approval (Rutledge, McCarthy, & Lendyak, 2014), resulting in perceptions of a permissive social context for pregaming. Thus, providing corrective normative feedback on overestimations of pregaming among similar peers may be expected to alter students’ perceptions of how often their peers drink and how much alcohol they consume while doing so, in which case changes in pregaming norms may also be expected to change, and perhaps mediate, intervention effects on pregaming behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Many college students tend to overestimate both descriptive and injunctive norms, which in turn may lead students to increase their drinking habits to match elevated drinking norms (12). Descriptive norms have also been shown to play a role in pregaming (13,14), and some research suggests that injunctive norms for pregaming might significantly impact pregaming participation in male students, but not female students (15). That said, little else is known about the impact of injunctive norms on participation in other risky drinking behaviors such as drinking games and tailgating.…”
Section: Introductionmentioning
confidence: 99%
“…In Caudwell and Hagger's (2015) study, greater perceived approval from others about one's engagement in pregaming was correlated with pregaming frequency and predicted pregaming via greater intentions to pregame (Caudwell & Hagger, 2015). In Rutledge, McCarthy, and Lendyak (2014), pregame-specific injunctive norms was a significant predictor of alcohol consumed while pregaming (i.e., pregaming quantity) among men, independent of pregaming descriptive norms. Still, results were far from conclusive; pregaming injunctive norms, after controlling for pregaming descriptive norms, did not predict pregaming quantity among women or pregaming frequency with respect to either gender.…”
Section: Introductionmentioning
confidence: 78%
“…Rutledge and colleagues (2014) found that descriptive norms related to the quantity of typical students' alcohol consumption while pregaming (but not frequency) was associated with past year pregaming frequency, after controlling for pregaming injunctive norms, in college women but not men. Further, as mentioned previously, Burger and colleagues (2011) demonstrated that women, but not men, responded to artificially low descriptive norms feedback by reducing frequency of pregaming relative to same-sex controls.…”
Section: Introductionmentioning
confidence: 84%